2011
DOI: 10.1111/j.1442-9071.2011.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetic retinopathy in indigenous Australians within Central Australia: the Central Australian Ocular Health Study

Abstract: Background: To estimate the incidence of diabetic retinopathy (DR) within the indigenous Australian population living in Central Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Because the real-world cohort was restricted to patients already exhibiting DR, the expected time from diagnosis of DM to onset of mild non-proliferative retinopathy was determined from local administrative data, showing a 7.7% annual incidence. This is in line with estimates from the literature, with various reports showing incidence rates of 8.0%–8.4% in recent Australian populations [16], 3.9%–7.1% in a population of Medicaid patients from the 1990s [17]. The second is for transition from proliferative retinopathy (state 3) to vision loss (state 4)for which rates were taken to be 0.7%, annualized from published incidences [18].…”
Section: Methodssupporting
confidence: 83%
“…Because the real-world cohort was restricted to patients already exhibiting DR, the expected time from diagnosis of DM to onset of mild non-proliferative retinopathy was determined from local administrative data, showing a 7.7% annual incidence. This is in line with estimates from the literature, with various reports showing incidence rates of 8.0%–8.4% in recent Australian populations [16], 3.9%–7.1% in a population of Medicaid patients from the 1990s [17]. The second is for transition from proliferative retinopathy (state 3) to vision loss (state 4)for which rates were taken to be 0.7%, annualized from published incidences [18].…”
Section: Methodssupporting
confidence: 83%
“…Furthermore, only 33% of Indigenous DR cases identified to benefit from laser photocoagulation from the SAEHP actually underwent treatment . A meta‐analysis of international studies conducted from 1975 to 2008 in patients not yet treated for DR showed that rates of progression to PDR and severe vision loss are substantially lower since 1985 compared with the pre‐1985 era . Differences are partly explained by more severe levels of DR at baseline and poorer glycaemic control prior to 1985.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,21 A meta-analysis of international studies conducted from 1975 to 2008 in patients not yet treated for DR showed that rates of progression to PDR and severe vision loss are substantially lower since 1985 compared with the pre-1985 era. 6,16,31 Differences are partly explained by more severe levels of DR at baseline and poorer glycaemic control prior to 1985. A more rapid progression to VTDR for Indigenous Australians for the same underlying reasons may explain the equal rates of VTDR between Indigenous and non-Indigenous Australians with DM, despite lower rates of any DR seen in Indigenous Australians from the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though numerous risk factors have been described in the literature influencing the rapid and unprecedented rise in T2DM prevalence rates in Indigenous populations around the globe [26], fragmented and insufficient data are available on the factors contributing to many of the downstream complications such as retinopathy [6]. For example, large population-based studies to date have only provided evidence for the epidemiology of DR alongside investigations into a narrow range of risk factors, which have identified geography (remote, OR 2.46), diabetes duration (OR 1.69), and a glycosylated haemoglobin percentage (HbA1c) above 7% as being associated with having DR among Indigenous Australians [15,27]. These studies have not investigated the complex T2DM/DR phenotype and the underlying social, psychological, environmental, behavioural, clinical, biological, metabolomic and genetic risk factors.…”
Section: Addressing the Knowledge Gapsmentioning
confidence: 99%
“…The risk factors of interest to sight-threatening DR may be fundamentally psychosocial, environmental, clinical, biological or genetic in nature, but are best interpreted together given the complexity of the T2DM phenotype and its vascular complications [18,28]. Non-modifiable and modifiable risk factors such as living remotely, duration of diabetes, increasing age, access to health care and poor glycaemic control are likely to also play an important role in the development of sight-threatening DR [15,27]. However, health inequities based on gender and socioeconomic standing can further influence the wellbeing of an individual, with reports suggesting that socioeconomic factors alone could explain more than two-thirds of the global variation in prevalence of vision impairment and blindness [29].…”
Section: Addressing the Knowledge Gapsmentioning
confidence: 99%